A comparison of traditional plant knowledge between students and herders in northern Kenya - Bruyere, Brett L., author; Trimarco, Jonathan, author; Lemungesi, Saruni, author; BioMed Central Ltd, publisher (Colorado State University. Libraries, 2016)
Background: The Samburu region of northern Kenya is undergoing significant change, driven by factors including greater value on formal education, improvements in infrastructure and development, a shift from community to private ownership of land, increased sedentary lifestyles and global climate change. One outcome of these changes are an increasingly greater likelihood for adolescent boys to be enrolled in school rather than herding livestock on behalf of the family in a landscape shared with numerous native vegetation and wildlife species. Methods: This study compared identification and knowledge of native plant species between boys enrolled in school with boys of similar age but primary responsibility as herders, called moran. Study participants walked an approximately 100 m path with 10 flagged points in which they were asked to identify any plant species at that point and associated facts of each species, within a 1 m radius. Results: On average, moran identified 38 species compared to 20 for students, including nearly 13 (of a possible 15) species considered to have high cultural significance. Students identified an average of 8.6 culturally-significant plants. Further, moran shared nearly 18 correct facts about the plants, compared with ten for students. In addition, herding frequency was the only significant predictor of plant identification in a linear regression. Conclusion: The results demonstrate that while formal education undoubtedly provides benefits to students, attendance in school in lieu of the traditional role of herders has consequences on young men in Samburu related to ability to identify native and culturally-significant plants. This further shows the importance for communities like those in Samburu undergoing change need to develop alternative options to transmit local traditional knowledge to its younger generations.
Keywords: Samburu; Kenya; local knowledge; traditional ecological knowledge; moran; pastoralism; plants